Experimental and numerical investigation on destructive effect of gas pipeline buried in silty clay under surface explosion. Issue 4 (December 2021) - Tang, Qichen; Jiang, Nan; Yao, Yingkang; Zhou, Chuanbo; Wu, Tingyao
Identifying the damage effects of buried multiple-operating-pressure gas pipelines subjected to various magnitude blasting load is a prerequisite for pipeline safety assessment. In this study, the dynamic response and damage effect are assessed by a combination of both field experiments and numerical simulation. It is indicated that the error between the numerical calculation and the field measured data is small and the reliability of the model is high. The dangerous section of the whole pipeline lies directly below the explosion source. The peak particle velocity (PPV) and the peak particle effective stress (PES) on the explosion-prone side of the section are the largest. Moreover, the PPV and PES increase with the increase of the working pressure of the pipeline. Results show that the empty pipe with no working pressure is the safest state among various pipe working state. There is a certain functional relationship among the explosive charge on the ground surface, working pressure, and PES of the pipeline.